Sensitivity and Specificity of Neutrophil Gelatinase Associated Lipocalin as an Early Biomarker or Acute Kidney Injury - Andriani, Meili; , Zulkifli; Puspita, Yusni; , Theodorus (Perdatin Pusat, 2015)
in hospital. Incidence of AKI is about 60%–70% and mortality rate from those patients is 60%. AKI is diagnosed by measuring serum creatinine concentration, which is an unreliable and delayed marker of deterioration of kidney function. It’s rising occurs when a significant amount of renal function has lost. Neutrophil gelatinase associated lipocalin (NGAL) level in AKI patients can increase quickly and earlier compared to serum creatinine and could be as a marker for AKI. The purpose of this study was to assess the sensitivity and specificity plasma NGAL. A diagnostic test was conducted in ICU and high care unit (HCU) of RS Dr. Moh. Hoesin Palembang since December 2014 to February 2015. There were 53 subjects included. All samples were examined with Alere Triage® kit and serum creatinin. Data analysis were performed by receiver operating characteristic (ROC) using SPSS® version 22.0.and MedCalc version 12.7. This study shows that a cut-off point 150 ng/mL for plasma NGAL has sensitivity of 88%, specificity of 81%, positive predictive value of 88%, negative predictive value of 81% and accuracy of 85%. Examination of plasma NGAL is more sensitive and specific in determining the start time of the occurrence of AKI compared with serum creatinine examination.